Studi cross sectional tentang Depresi Pascakelahiran dan Faktor-faktor Risikonya pada Ibu Nifas Di Kabupaten Badung, Bali - Lindayani, I Komang; Nurmala, Ira; Puspitasari, Nunik; Prasetyo, Budi (Politeknik Kesehatan Kemenkes Mamuju, 2025)
Postpartum depression (PPD) affects many aspects of a mother's life. Understanding the factors that contribute to this condition is crucial, as some factors may play a greater role than others. This study aimed to identify the prevalence of PPD, examine its associated factors, and determine the dominant factors related to the incidence of PPD in Badung Regency, Indonesia. This research employed a cross-sectional design conducted between May and July 2024. It involved 239 mothers who were 2 – 6 weeks postpartum. Participants were selected from seven public health centers in Badung Regency using two-stage cluster sampling. A questionnaire was used to assess several factors, including sociodemographic characteristics, obstetric history, baby characteristics, stressors during the postpartum period, husband’s support, and postpartum depression symptoms. These factors were analyzed using bivariate chi-square analysis and multivariate logistic regression. The prevalence of PPD in this study was 47.3%. Associated factors included maternal age, stressors related to personal needs and fatigue, infant nurturing, body changes and sexuality, and instrumental and emotional husband support. Among these, the most dominant factors were body changes and sexuality, personal needs, and fatigue, which increased the risk of PPD by approximately threefold. The prevalence of PPD in Badung Regency is higher than previously reported in other areas. This highlights the importance of PPD screening and educating husbands about the need to provide both instrumental and emotional support during the postpartum period. We recommend implementing early screening and husband involvement programs.